ASSOCIATION BETWEEN SELF-EFFICACY AND ACADEMIC STRESS AMONG STUDENTS IN A FULL DAY SCHOOL SYSTEM - Alvy Nur Hidayati; Rhadika Wahyu Ningrum; Adelia Ika Cahyani (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Full day school is an educational policy that extends the duration of students' learning activities throughout the school day. The academic demands associated with this learning system may increase students' academic stress, particularly among those with lower levels of self-efficacy. Self-efficacy refers to an individual's belief in their ability to successfully perform specific tasks and achieve desired outcomes. This study aimed to examine the relationship between self-efficacy and academic stress among students enrolled in a full-day school system. A quantitative correlational study was conducted involving 105 students. Data were collected using a self-efficacy questionnaire based on a Likert scale, while academic stress was assessed using the Depression Anxiety Stress Scale (DASS-21). The relationship between self-efficacy and academic stress was analyzed using a correlation test. The findings revealed a statistically significant relationship between self-efficacy and academic stress (r = 0.191; p 0.05). Although the correlation was weak, the results indicate that self-efficacy was significantly associated with students' academic stress levels.